Frontal white matter integrity as an endophenotype for schizophrenia: diffusion tensor imaging in monozygotic twins and patients' nonpsychotic relatives - Camchong, Jazmin; Lim, Kelvin O.; Sponheim, Scott R.; MacDonald III, Angus W. (Frontiers in Human Neuroscience, 2009)
Diffusion tensor imaging (DTI) provides anatomical connectivity information by examining the directional organization of white matter microstructure. Anatomical connectivity and its abnormalities may be heritable traits associated with schizophrenia. To further examine this hypothesis, two studies were conducted to compare anatomical connectivity between (a) monozygotic (MZ) twin pairs and random pairings among twins and (b) first-degree relatives of schizophrenia patients and a healthy control group. Analyses focused on frontal regions of the brain following previous findings of anatomical connectivity abnormalities associated with schizophrenia. For Study 1, eighteen MZ twin pairs (11 female pairs, age: M=25.44, SD=5.69) were recruited. For Study 2, twenty two first-degree relatives of schizophrenia patients (14 females, age: M=48.50, SD=8.22), and 30 healthy controls (12 females, age: M=43.83, SD=11.39) were recruited. Fractional anisotropy (FA), a white matter directional organization metric, was measured with DTI. In Study 1, FA values were more strongly correlated between MZ twin pairs than between randomly generated pairs in genu of corpus callosum, anterior cingulum and forceps minor. In Study 2, relatives of schizophrenia patients showed reduced FA values in medial frontal white matter (p<0.05, corrected). The present study suggested that anatomical connectivity in medial prefrontal cortex appeared significantly heritable within MZ twin pairs, an important criterion in the development of an endophenotype. In addition, altered medial frontal white matter integrity found in non-affected relatives of schizophrenia patients seems to suggest that reduced white matter integrity in medial frontal regions of the brain might be associated with the genetic liability to schizophrenia.